Trends in the European Union's Circular Economy Action Plan - Volochai, Olga; Yastremska, Larysa; Korniienko, Iryna; Garkava , Kateryna; Kosoholova, Liudmyla; Kuznietsova, Olena; Baranovskyy, Mikhaylo (Problems of Environmental Biotechnology, 2024)
The trends of the European Union's Circular Economy Action Plan are analyzed